The Relationship Between Postpartum Mothers' Knowledge About Breast Care and Smooth Breast Milk Flow at The Millennium Clinic - Sri Putriani Sinaga; Dinar Manalu; Sunengsih; Lely Masnita; Nova SJ (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
The smooth provision of breast milk (ASI) during the postpartum period is still a challenge that needs special attention, one of which is influenced by the level of knowledge of mothers about breast care. This study aims to analyze the relationship between the level of knowledge of postpartum mothers about breast care and the smoothness of breastfeeding at the Millenium Clinic in 2024. This study used an analytical survey design with a cross-sectional approach. The population in this study were all postpartum mothers who visited the Millenium Clinic as many as 31 people (N = 31). The total population technique was used so that the entire population was used as a sample. The results showed that most postpartum mothers (19 respondents, 61.3%) had a low level of knowledge, while 7 respondents (22.6%) had a sufficient level of knowledge, and only 5 respondents (16.1%) had good knowledge. In addition, the majority of postpartum mothers (21 respondents, 67.7%) experienced poor breastfeeding, while 10 respondents (32.3%) reported smooth breastfeeding. The results of statistical analysis with a 95% confidence level showed a significant relationship between the level of knowledge of postpartum mothers about breast care and the smoothness of breast milk production (p < 0.001). It can be concluded that increasing postpartum mothers' knowledge about breast care is closely related to the smoothness of breast milk production. Therefore, it is recommended for health workers to develop comprehensive health promotion and education programs regarding breast care, especially for postpartum mothers in their respective work areas.